Letter - Le Gros Clark, F.
C02-0124-001 COMMITTEE AGAINST MALNUTRITION HON SECRETARY - F LE GROS CLARK 19c EAGLE STREET W C 1 - CHANCERY 7567 HON TREASURER - Mrs ANNE McNALLY 17 CHARLOTTE ST LONDON W 1 - MUSEUM 0994 1/ 6/37 Dear Dr Morgan, I think you will remember that at the annual meeting of the S.M.A. It was agreed that members should be asked to assist in the after-care work of casualties from the International Brigade. We have undertaken to help Brook in the initial stages and to get the matter centralised. So far it is going well, though of course there is only a trickle of cases. I send you a copy of the rough provisional scheme. At Hastings' suggestion I wrote to Sir Ambrose Woodall, who replies in kind terms referring me to you. I should in any case have written you. But here it is a question of the general assistance we might hope to receive from the Manor House. I do not know enough about the regulations. We have a reasonable number of specialists on our panel now. But, if I might reduce the matter to a precise inquiry, we should like in my opinion to strengthen our list of consultant surgeons and orthopedic specialists; and it is possible that you might know of one or two who would readily co-operate in such a scheme as this from their general sympathies. Secondly I think we ought to make a preparatory solution of the possible problem of artificial limbs. There are sure to be a few cases of this description. Funds will no doubt be available for purchase, but suitable fitting is an important matter. I had not made such precise inquiries from Sir Ambrose Woodall; but I am sure you will advise on them, so far as you can. I can of course write direct to any names you can let me have. With good wishes. Yours sincerely, F. Le Gros Clark 292C/946/2/124